Spontaneous Bilateral Hemothorax as a Case of Epithelioid Hemangioendothelioma (EHE) - Essa M. AlGhunaim; Hafsa AlNajem; Derar S. AlShehab (Case Reports in Oncological Medicine)
Epithelioid hemangioendothelioma (EHE) is a rare tumor that is vascular in origin, arising from the endothelial or preendothelial cells. It can occur at different sites of the body, commonly in the liver, lungs, and bone. Pulmonary EHE is usually symptomatic, sometimes presenting with a cough, dyspnea, or chest pain. Rarely, it presents with pleural effusion. Here, we are presenting a case of pleural epithelioid hemangioendothelioma presenting as a case of spontaneous bilateral hemothorax.